Investigative actions in Ukraine, Germany and France: comparative legal analysis of regulations and application practices - A. A. Shyshenko (Аналітично-порівняльне правознавство)
Investigative actions are important in criminal proceedings because they ensure the effective investigation of criminal offenses, the collection of evidence and the observance of human rights throughout the process. However, the legal regulation and practice of conducting them have really clear differences from country to country, which in turn necessitates a comparative legal analysis in this area. Ukraine applies investigative procedures in accordance with the changes introduced after the reform of the criminal procedure legislation, but there are still relevant issues to ensure and maintain a balance between human rights and interests of justice. The legislations of Germany and France, as well as the relevant court practice on conducting investigative actions in these countries, ensure an appropriate level of guarantees for participants in the criminal process. The purpose of this study is to compare the legal regulation and practice of criminal procedure in Ukraine, Germany and France, and to identify effective approaches to improving the national criminal procedure. This article describes the study of key investigative actions, their peculiarities in each of the above-mentioned countries, and the mechanisms for ensuring the legality of the process and protection of human rights during the performance of investigation. Particular attention is paid to the role of judicial control over the investigative process, the standard of admissibility of evidence to cases and procedural guarantees for participants in the criminal process. The results of the study can be used to draw conclusions about the strengths and weaknesses of each of the legal systems under consideration. For example, Germany pays considerable attention to judicial control over investigative actions, and this contributes to the observance of human rights. The French system of investigative actions combines elements of continental and Anglo-Saxon law, which ensures the high efficiency of criminal investigations thanks to the judge-instructor. In Ukraine, despite the recent reform of the criminal procedure system, there are a number of problems in the areas of judicial control, namely the insufficient level of the latter and frequent violations of the rights of participants within investigative actions. The comparative legal analysis can be used to formulate recommendations for improving the Ukrainian system of investigative actions, taking into account the experience and mistakes of European countries. Improving the efficiency of pre-trial investigation, ensuring the proper level of rights of all participants in the process and strengthening trust in law enforcement agencies can be the basis for the Ukrainian criminal process by adopting the best practices of the European Union.